Three new HLA class I alleles with synonymous mutations: HLA‐A*03:01:62, ‐C*07:02:82 and ‐C*12:03:42. (10th November 2017) - Moya‐Quiles, M. R.; Balas, A.; Muro, M.; García‐Alonso, A. M.; Vicario, J. L.
Abstract : Three new HLA class I alleles with synonymous mutations were identified.